Spatial effects and influencing factors of urban land intensive use in the Yangtze River Delta under high-quality development - Luo, Xiang; Qin, Jingjing; Cheng, Chao; Pan, Yue; Yang, Tiantian (Frontiers in Environmental Science, 2022)
To integrate the concept of high-quality development into urban land use, this paper explores the spatial-temporal pattern characteristics of urban land intensive use (ULIU) in the Yangtze River Delta with a constructed evaluation index system, the comprehensive evaluation model and exploratory spatial data analysis based on the spatial panel data of 41 cities from 2010 to 2020. The paper also analyzes the spatial effects and influencing factors of ULIU with the spatial Durbin model and partial differential method. The results demonstrate that: 1) The ULIU in the Yangtze River Delta generally showed consistent growth from 2010 to 2020. However, there was significant spatial differentiation among different regions, as the land intensive use level was higher in cities along the Yangtze River and coastal cities around Hangzhou Bay, while relatively lower in the mountainous and hilly cities in Zhejiang and southwestern Anhui. 2) The ULIU level showed significant positive global spatial autocorrelations, while its local spatial characteristics mainly included four types dominated by high-high agglomeration and low-low agglomeration from 2010 to 2020. 3) Economic development, industrial structure and infrastructure could remarkably promote the ULIU of both local and neighboring cities. Scientific and technological innovation could significantly enhance the ULIU of local cities; population urbanization and government financial pressure showed significant negative effects on the ULIU of local cities; while all the above three factors had insignificant effects on the ULIU of neighboring cities. These findings are of great significance for revealing the internal mechanism underlying the spatial effect of land intensive use and provide some guidance for improving the level of ULIU in the Yangtze River Delta from the perspective of regional cooperation.